Phonemic word fluency is related to temporal and striatal gray matter volume in healthy older adults - Grönholm-Nyman, Petra; Saarela, Carina; Ellfolk, Ulla; Joutsa, Juho; Parkkola, Riitta; Laine, Matti; Karrasch, Mira; Rinne, Juha O. (Taylor & Francis, 2025)
Word fluency (WF) tasks that tap verbal and executive function show deteriorating performance by advancing age. To address the scarcely studied age-related brain correlates of WF, we employed whole-brain voxel-based morphometry to examine gray matter (GM) correlates of semantic and phonemic WF in 46 healthy older adults. Lower phonemic WF score was related to smaller anterior medial temporal GM volume as well as smaller GM volume in the putamen bilaterally. A disproportionally weak score on phonemic WF in relation to semantic WF was associated with smaller GM volume in the left inferior frontal cortex, the right anterior medial temporal lobe, and the right striatum. There were no significant associations for semantic WF. The fact that our temporal and subcortical findings were bilateral and right-lateralized, may reflect age-related compensation by these brain areas.